High-order species interactions shape ecosystem diversity - Eyal Bairey (Nature Portfolio, 2016)
A major challenge of theoretical ecology is explaining the stable coexistence of diverse multi-species communities. Here, the authors show that when the interactions among two species depend on the presence of other species, the diversity of the community becomes a necessity rather than an obstacle for its stability.